A descriptive study on the qualification of dental laboratory technicians in Manila and Makati City in accordance with the Philippine Dental Act of 2007 - Modina, Christina S.; Quiaoit, Charlene B.; Rebueno Santos, Jessica K. (Adviser).
The Philippine Dental Act of 2007 is a new guideline that has involved the regulation of dental technologists and hygienists other than the dentists. This study focused on the qualifications of dental laboratory technicians, who are, most of the time, the ones responsible for the fabrication of fixed and removable partial dentures, complete dentures and orthodontic appliances. Thus, their capability has an effect on the final products associated with services rendered by dentists. The study determined the qualifications of dental technicians based on the new law (Philippine Dental Act of 2007), having the following requirements: (1) a citizen of the Philippines; (2) possesses good moral character; (3) has finished the 2-year certificate in dental technology conferred by a recognized and legally constituted college, or school of dentistry registered with the TESDA; (4) has undergone on-the-job training in a registered/accredited dental laboratory for at least 6 months. In order to be qualified, one must obtain the four requirements stipulated. Once these four requirements are satisfied, one can take the Board Exam for Dental Technicians. A descriptive study was done on eighty-one randomly chosen dental technicians in dental laboratories in Makati and Manila. No special qualifications were required for the dental technicians to participate in the study. Dental technicians, who were present and willing to be part of the study, were given questionnaires to answer after informed consents were signed. The results were tallied and described in percentages, ranges and mean averages. All of the subjects are Filipino citizens, 51% possess good moral character, 10% have 2-year certificate and 30% underwent on-the-job training. Only 3 out of the 4 criteria were satisfied by majority of the subjects making them not qualified based on the Philippine Dental Act of 2007. In addition, 74% of the total population is aware of the new law. Only 4.9% are qualified dental technicians who may take the board exam. Based on the gathered data, dental technicians in Manila and Makati are not qualified in accordance with the Philippine Dental Act of 2007.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental technicians